(untitled) (Nusantara: Journal of Law Studies, 2026)
The halal industry has evolved into a global economic regime that demands governance based not only on normative compliance but also on the ability to guarantee process integrity and business sustainability. However, in the small and medium enterprise (SME) sector, halal certification is still dominated by administrative compliance that has not been integrated into operational systems. This study aims to analyze the implementation of halal certification policies in SMEs by integrating the maqāsid al-sharī’ah (Islamic principles) and risk-based governance perspectives. This study employed a qualitative case study design and used document analysis, in-depth interviews, and observations in Padang Panjang City. The results revealed a structural gap between policy design and implementation practices. This gap is reflected in the low halal certification rate of 3.9% (520 out of 13,183 SMEs), the prevalence of self-declaration schemes (93.8%), and weak halal literacy and underdeveloped risk-based control systems in the production process. These conditions suggest that halal compliance remains largely symbolic and has yet to yield substantive outcomes in line with the maqāsid. This study contributes to the field by developing an integrative analytical framework that connects maqāsid, as the normative basis, with risk-based governance, as the operational mechanism. The framework emphasizes the need to shift from rule-based compliance to system-based governance in halal policy. This study introduces the Maqāsid-Based Risk Governance Index (MRGI), an integrative model that uses operational indicators such as safety, traceability, and transparency to measure the achievement of maqāsid outcomes.